PENGARUH KUALITAS LAYANAN DAN CITRA TERHADAP KEPUASAN DAN LOYALITAS APARATUR DESA PADA DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN WAKATOBI (The Influence of Service Quality and Image on Satisfaction and Loyalty of Village Apparatus at the Office of Women's Empowerment, Child Protection, Community and Village Empowerment, Wakatobi Regency) - La Ode Ibrahim; Rahmat Madjid; Sinarwaty Sinarwaty (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to determine the effect of service quality and image on satisfaction and loyalty and to examine the mediating effect of satisfaction on service quality and image on the loyalty of village officials in Wakatobi Regency. This study takes the object at the Department of Women's Empowerment, Child Protection, Community Empowerment and Rural Wakatobi. The population in this study were all village officials in Wakatobi district, the sample of this study amounted to 75 village officials in Wakatobi Regency. Data collection using questionnaires and data analysis tools using Partial Least Square (PLS).The results of this study can be concluded that service quality has a positive and significant effect on satisfaction. Service quality has a positive and significant effect on loyalty. Image has a positive and significant effect on satisfaction. Image has a positive and significant effect on loyalty. Satisfaction has a positive and significant effect on loyalty. Satisfaction mediates the effect of service quality on loyalty and the type of mediation is partial mediation. Satisfaction mediates the effect of image on loyalty and the type of mediation is partial mediation.